Integral Scientific Advice for Outbreak Response: Lessons learned from an Avian Influenza Simulation in the Netherlands - Dr Anja Schreijer; Dr. Femke Overbosch; Dr. Tomris Cesuroglu; Dr Charlotte Waltz; Drs. Bart Blokland; Drs Jeanette de Boer; Drs Tim Florschutz (International Journal of Infectious Diseases)
Background: The continuing avian influenza outbreaks in animals pose a public health threat worldwide. Concerns about the risk for humans are raising, now we see spread among different mammal species and animal to human transmission. The question raises how governments are best advised about this impending outbreak. One of the lessons learned from the COVID-19 pandemic is that future pandemics demand swift and effective collaboration across disciplines to address diverse consequences and priorities. In many countries the governance framework for outbreaks requires different disciplines to provide advice separately to the government. We conducted an avian influenza outbreak simulation to explore development of integrated scientific advice in pandemics. Methods: We organised two simulation events on 17 April and 24 May 2024. Prior to the simulation exercise, literature research and in-depth interviews were conducted with experts. During the simulations, the scenario dealt with different phases of the start of a pandemic situation due to a novel influenza virus from zoonotic origin. The scenario on 17 April depicted a variant of avian influenza spreading via pigs, including the first cases with human-to-human transmission, triggering significant health implications for humans and animals. In May the simulation continued with widespread human-to-human and cross-border transmission, hence the start of a new pandemic. A best- and worst-case scenario was illustrated from a biomedical and social-economic viewpoint. On both events, 20-23 Dutch experts from different disciplines initially crafted their recommendations independently. Three interdisciplinary groups then converged, utilizing an evidence-to-decision framework. Thematic analysis was conducted on notes of group and plenary discussions, and reflection and evaluation sessions. Results: The interdisciplinary discussions helped participants identify the blind spots within the disciplinary recommendations. A sense of urgency differed between sectors, leading to diverse point of focus within the expert teams. The biomedical team focussed on limiting the spread of the virus, while the the social-economic team focussed on mitigating the impact of the outbreak within society. Hence, the biomedical team advised measures like a local lockdown and active surveillance, where the social economic team preferred citizen consultations, exploration of economic and mental support and proper communication.During integrative discussion, the various disciplines brought valuable insights from respective sectors, converging the different views towards a shared focus and creating mitigating advice.For example, the integral advice provided various mitigating measures to interventions with a large social impact, e.g. setting up an auxiliary structure to quickly identify and support vulnerable groups and setting up tailored communication structures. Conclusions: Interdisciplinary discussions are needed in pandemic advice to identify blind spots within the disciplinary recommendations. Preparedness and alignment of guidelines in the different expert fields will support a shared focus and pace of action in case of an outbreak and lead to better pandemic preparedness.